Determinan terhadap nilai perusahaan dengan kinerja keuangan sebagai pemoderasi pada perusahaan yang terdaftar di Bursa Efek Indonesia - Trihandayani, Urip; Badjuri, Achmad (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the influence of Good Corporate Governance, Corporate Social Responsbility on Company Value and Financial Performance as moderation. This study used purposive sampling methods from 20 agriculture, minning, and manufacture companies listed on the IDX and made sustainability reports in the period 2018 to 2020. Data testing is performed with moderated regression analysis (MRA) techniques. The results of this study showed that the number of independent commissioners, and audit committees had a significant positive effect on the value of the company while institutional ownership, board of commissioners, and CSR had no significant effect on the value of the company. Financial performance can moderate the influence of institutional ownership and audit committees on the value of the company whereas financial performance cannot moderate the influence between independent commissioners, boards of commissioners, and CSR on the value of the company.